On the identification of relative wage rigidity dynamics: a proposal for a methodology on cross-section data and empirical evidence for Poland in transition - Patrick A. Puhani (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
We present a new and simple empirical methodology to identify relative wage rigidity dynamics. The methodology is applied to data from the Polish Labour Force Survey for the period 1994 to 1998. We estimate ceteris paribus changes in relative wage and unemployment differentials for various labour market defining characteristics. A simultaneous increase in the relative wage and the unemployment likelihood is defined as a relative wage rigidity dynamic for a labour market characteristic. We find that the Polish wage structure generated hardly any rigidities between 1994 and 1998 nor did it reduce possibly existing rigidities during that period.
Keywords: P20; J31; J64; 330; wages; unemployment; rigidities; identification; Poland; Lohnrigidität; Lohnstruktur; Arbeitslosigkeit; Übergangswirtschaft; Schätzung; Polen